2018
DOI: 10.1136/bcr-2017-223518
|View full text |Cite
|
Sign up to set email alerts
|

Uterocutaneous fistula following B-Lynch suture for primary postpartum haemorrhage

Abstract: A 30-year-old woman, who had undergone emergency lower segment caesarean section (LSCS) for failed induction 2 months back, presented with a fistulous opening along with discharge from her previous incision scar. She had developed a massive primary postpartum haemorrhage at the time of LSCS 2 months back, which was managed with B-Lynch suture and vessel ligation. Fistulogram revealed a connection between the uterus and the skin. The diagnosis was confirmed by a contrast-enhanced CT scan. Patient was subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 10 publications
0
9
0
10
Order By: Relevance
“…Our case includes two of the reported risk factors: repetitive C/S and wound infection in the early postoperative period. Although uterocutaneous fistulas are reported to occur at least 2 months after surgery [8,9], in this case, symptoms appeared as early as 1 month after the last C/S, with no additional predisposing factors found.…”
Section: Commentarymentioning
confidence: 60%
“…Our case includes two of the reported risk factors: repetitive C/S and wound infection in the early postoperative period. Although uterocutaneous fistulas are reported to occur at least 2 months after surgery [8,9], in this case, symptoms appeared as early as 1 month after the last C/S, with no additional predisposing factors found.…”
Section: Commentarymentioning
confidence: 60%
“…Cases of post-partum hemorrhage wherein B-lynch sutures are placed have high risk of scar dehiscence, which may result in uterocutaneous fistula (6,7) . Other rare causes that may result in the formation of uterocutaneous fistula are patients with multiple abdominal myomectomies, history of hysterectomy, and as a primary presentation in underlying gynecologic malignancy such as endometrioid adenocarcinoma, which can predispose the weak cesarean scar to fistula formation (6,7,8) . The blood leakage from the incision site during menstruation has been described as pathognomonic of the uterocutaneous fistula (9) .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the reported cases of uterocutaneous fistula were found following surgical intervention such as cesarean delivery or treatment for miscarriages. Thakur et al reported a 30-yearold lady, who developed uterocutaneous fistula after undergoing emergency lower segment caesarean section for failed induction 2 months back, and developed a massive primary postpartum hemorrhage at the time of cesarean section which was managed with B-Lynch suture and vessel ligation and Limp et al reported a 33 year-old lady who had an emergency cesarean section for retained second twin which was complicated by utero-cutaneous fistula due to red degeneration of intramural fibroids [1,3]. In one recent case series by Rezaei et al there was co-existence of uterocutaneous fistula and vesico-cutaneous fistula ("twin fistula") in a multiparous lady with two previous cesarean sections [9].…”
Section: Discussionmentioning
confidence: 99%
“…A fistula may be defined as an abnormal communication between two epithelium-lined surfaces [1]. Most uterine fistulae are between the uterus and the bowel or bladder (uterocolonic or uterovesical) due to postoperative injuries or infectious conditions [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation